Home learning environment and physical development impact children’s executive function development and literacy in rural Côte d’Ivoire - Jasińska, Kaja; Zinszer, Benjamin; Xu, Zizhuo; Hannon, Joelle; Seri, Axel, Blahoua; Tanoh, Fabrice; Akpe, Yapo, Hermann (My University, 2022)
Socio-economic status (SES) is closely linked to children’s reading development. Previous research suggests that executive functions (EF) mediate the effects of SES on reading, however, this research has almost exclusively focused on high-income countries (HICs). Comparatively less is known about the mechanisms that link SES and literacy in low-and-middle-income countries (LMICs). Childhood experiences of poverty in LMICs have been consistently linked to cognitive development through two sets of predictors: nutrition and physical growth, and the availability of educational scaffolding at home. The influence of the home learning environment (i.e. material deprivation, types of caregiver interactions) and nutrition to support children’s physical development (i.e. children’s BMI and stature for their age) on EF and literacy was examined in 630 primary-school children (6-14 years) in rural Côte d'Ivoire, West Africa. Structural equation modeling revealed that SES had an indirect effect on EF via the home learning environment, and in turn, reading. Importantly, the home learning environment, and a child’s physical development and nutrition showed distinct contributions to EF. The results suggest that improved educational scaffolding at home and supplemented nutrition could support EF development and reduce the negative impact of socioeconomic risk factors on reading.
Supplemental Materials: https://osf.io/wmbg8/
Keywords: Côte d’Ivoire; Executive function; Literacy; Socio-economic status (SES)